How Clean Is the Linen at My Hospital? The Mucorales on Unclean Linen Discovery Study of Large United States Transplant and Cancer Centers. (9th October 2018) - Sundermann, Alexander J; Clancy, Cornelius J; Pasculle, A William; Liu, Guojun; Cumbie, Richard B; Driscoll, Eileen; Ayres, Ashley; Donahue, Lisa; Pergam, Steven A; Abbo, Lilian; Andes, David R; Chandrasekar, Pranatharthi; et al.
Abstract: Mucormycosis outbreaks have been linked to contaminated linen. We performed fungal cultures on freshly-laundered linens at 15 transplant and cancer hospitals. At 33% of hospitals, the linens were visibly unclean. At 20%, Mucorales were recovered from >10% of linens. Studies are needed to understand the clinical significance of our findings.